Hey Alexa, launch Twitch : using sport sponsorship to drive business development - Declercq, Lindee; Dalal, Keegan; Piché, Megan C.; Burton, Nicholas; Naraine, Michael L., 1987- (London : Human Kinetics, Inc., 2021)
This fictional case looks at Amazon using sports sponsorship to expand business operations into the Middle East. As part of Amazon's plan to grow internationally, it bought Souq, a Dubai-based e-commerce platform, in 2017 for $580 million, becoming Amazon's largest international acquisition. Now that it has been rebranded as "amazon.ae," Amazon wants it to become the leading e-commerce site in the Middle East. To do this, it is seeking out sponsorship options, deciding sports sponsorship is the best choice. As Twitch was purchased by Amazon in 2014 for nearly $1 billion, it has become the target sports organization. Twitch, a live video-game-streaming site, has become a leader in the development of eSports. Its 15 million daily users spend an average of 95 min on the site each day, more than double the time of YouTube users. For Amazon, Twitch will provide access to young demographic that they can turn into amazon.ae users.The primary purpose of this case study is to introduce students in sponsorship to how sport can be used as a tool to drive business development. The Middle East was selected as the region of focus due to the increased interest in sport from its political leaders. As Amazon seeks to break into this new market, they will follow suit using Twitch as their sports property. Students will be required to explore the pros and cons of developing a strategic partnership in an online space.
Includes bibliographical references.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sports sponsorship -- Case studies; Electronic commerce -- Marketing -- Case studies